KOMUNIKASI INSTRUKSIONAL INSTRUKTUR PADA PROGRAM PEALTIHAN MENJAHIT PAKAIAN DI BALAI LATIHAN KERJA (BLK) PEKANBARU - Absah, Siti; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Training is one of the programs that are run by the Hall Practice work (BLK) Pekanbaru. In learning to use the instructional communication instructors on class sewing clothes that are capable of processing the fabric into garments such as kebaya, skirts, aprons, shirts and more. Industry around Soweto even industries that are outside the city are keen to make trainee to become employees. For current alumni trainee sewing clothes is already a lot of work in the industry and Dumai Pekanbaru, Pelalawan, Kuansing, Siak. As for the purpose of this research is to know the methods of learning, media of learning and communication barriers in instructor training courses instructional class sewing clothes at Work Exercise Hall (BLK) Pekanbaru.This research uses qualitative research methods. Research on lakukkan in a work Practice Hall (BLK) Pekanbaru. The selection of done informant with purposive technique. Data collection techniques used during the research is by way of observation, interviews, and documentation. While the validity of data that researchers use is extend participation, triangulation. The results showed that the instructional communication method used by instructors in the sewing clothes class at the Pekanbaru Training Center (BLK) was using the command method, training method / practice, and the question and answer method. While instructional communication media used by instructors in the form of visual media are pictures and whiteboards and media tools. Meanwhile, the instructional communication barriers that occur in the class are sewing clothes in the form of obstacles to the technical media and barriers that come from psychological communicants.